Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.

Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

MoS2 nanoparticles and h-BN nanosheets from direct exfoliation of bulk powder: one-step synthesis method - Thripuranthaka, M.; Rout, Chandra Sekhar; Late, Dattatray J. (Materials Research Express, 2014)
We report facile synthesis of MoS2 nanoparticles and h-BN nanosheets using ultrasonication method in suitable solvents such as N-Methyl-2-pyrrolidone and ethylene glycol, respectively. The average size of MoS2 nanoparticles observed from TEM analysis were 4-5 nm and about a few hundreds of nm for h-BN nanosheets. Raman spectroscopy carried out on nanoparticle samples confirms the formation of MoS2 nanoparticles and h-BN nanosheets. UV-vis absorption and photoluminescence (PL) measurements carried out on the products show typical absorption and luminescence spectra of MoS2 and h-BN. Further, we attempted to decorate gold nanoparticles on nanosheets of MoS2 and h-BN which show subsequent change in Raman spectra due to charge transfer interaction.
Keywords: h-BN; MoS2; Nanoparticles; nanosheets; Optical properties

Negative infrared photocurrent response in layered WS2/reduced graphene oxide hybrids - Ratha, Satyajit; Simbeck, Adam J.; Late, Dattatray J.; Nayak, Saroj K.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
We report high performance IR photocurrent response of two-dimensional hybrid materials consisting of layered WS2 nanosheets and reduced graphene oxide (RGO). Comparative photocurrent response studies of WS2 nanosheets, RGO, and WS2/RGO hybrids were carried out by performing current-voltage (I-V) and time-dependent current measurements with a laser excitation source having a wavelength of 808 nm. The experimental investigations indicate that WS2/RGO hybrids show negative photocurrent response, whereas WS2 and RGO show positive photocurrent response. The negative photocurrent response of the WS2/RGO hybrids is explained using a band alignment diagram and attributed to a charge transfer mechanism between WS2 and RGO. This analysis is further corroborated by first-principles density functional calculations. The fabricated device based on WS2/RGO hybrids shows a photosensitivity R-lambda of about 6 AW(-1) and a quantum efficiency eta of similar to 924%, which demonstrates high sensitivity of the hybrid material towards IR detection. WS2/RGO hybrids are therefore promising candidates for potential applications in optoelectronic circuits and low cost, high performance, and reliable photodetectors. (C) 2014 AIP Publishing LLC.

Temperature dependent Raman spectroscopy of chemically derived few layer MoS2 and WS2 nanosheets (vol 104, 081911, 2014) - Thripuranthaka, M.; Kashid, Ranjit V.; Rout, Chandra Sekhar; Late, Dattatray J. (Applied Physics Letters, 2014)

Temperature dependent Raman spectroscopy of chemically derived few layer MoS2 and WS2 nanosheets - Thripuranthaka, M.; Kashid, Ranjit V.; Rout, Chandra Sekhar; Late, Dattatray J. (Applied Physics Letters, 2014)
We have systematically investigated the temperature dependent Raman spectroscopy behavior of a few layered MoS2 and WS2 nanosheets synthesized using simple hydrothermal method. Our result reveals A(1g) and E-2g(1) modes soften as temperature increases from 77 K to 623 K. This behavior can be explained in terms of a double resonance process which is active in single-and few layer thick nanosheets. The frequency shifts and peak broadening can provide unambiguous, nondestructive, and accurate information of a few layered MoS2 and WS2. This mechanism can also be applicable in characterizing the structural, optical, electronic, and vibrational properties of other emerging layered materials. (c) 2014 AIP Publishing LLC.

Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Enhanced field emission of plasma treated multilayer graphene - Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2015)
Electron emission properties of multilayer graphene (MLG) prepared by a facile exfoliation technique have been studied. Effect of CO2 Ar, N-2, plasma treatment was studied using Raman spectroscopy and investigated for field emission based application. The CO2 plasma treated multilayer graphene shows an enhanced field emission behavior with a low turn on field of 0.18 V/mu m and high emission current density of 1.89 mA/cm(2) at an applied field of 0.35 V/mu m. Further the plasma treated MLG exhibits excellent current stability at a lower and higher emission current value. (C) 2015 AIP Publishing LLC.

Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Recent developments in 2D layered inorganic nanomaterials for sensing - Kannan, Padmanathan Karthick; Late, Dattatray J.; Morgan, Hywel; Rout, Chandra Sekhar (Nanoscale, 2015)
Two dimensional layered inorganic nanomaterials (2D-LINs) have recently attracted huge interest because of their unique thickness dependent physical and chemical properties and potential technological applications. The properties of these layered materials can be tuned via both physical and chemical processes. Some 2D layered inorganic nanomaterials like MoS2, WS2 and SnS2 have been recently developed and employed in various applications, including new sensors because of their layer-dependent electrical properties. This article presents a comprehensive overview of recent developments in the application of 2D layered inorganic nanomaterials as sensors. Some of the salient features of 2D materials for different sensing applications are discussed, including gas sensing, electrochemical sensing, SERS and biosensing, SERS sensing and photodetection. The working principles of the sensors are also discussed together with examples.

Effect of plasma treatment on multilayer graphene: X-ray photoelectron spectroscopy, surface morphology investigations and work function measurements - Patil, Urmila V.; Pawbake, Amit S.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Jadkar, Sandesh R.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report here the effect of plasma treatment on multilayer graphene samples as determined by X-ray photoelectron spectroscopy and surface morphology studies with atomic force microscopy, scanning electron microscopy and transmission electron microscopy. The plasma treatment was modified to introduce controlled levels of defects and functionalities to the graphene samples to give tunable properties. The elemental composition and structure were investigated by XPS and micro Raman spectroscopy. The XPS study showed that there was a slight variation in the sp(2)/sp(3) hybridization ratio between the plasma-treated samples and the pristine sample. Kelvin probe measurements were carried out on all the multilayer graphene samples and indicated a slight variation in the work function of the graphene samples after plasma treatment.

Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.

SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.

Electrochemical synthesis of a ternary transition metal sulfide nanosheets on nickel foam and energy storage application - Sahoo, Surjit; Naik, Kusha Kumar; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Alloys and Compounds, 2017)
We report growth of nickel cobalt sulfide (NCS) ultrathin nanosheets directly on Ni foam substrate by a facile and novel electrodeposition method. The as-prepared NCS sample is used as an electrode material for supercapacitor application due to their large electrochemically active surface area and interconnected nanosheet channels for the facilitation of ion transportation. The NCS nanosheets possess enhanced electrochemical performance in terms of fast and high reversible faradaic reactions characterized by prominent oxidation and reduction peaks. NCS nanosheets showed an ultrahigh specific capacitance of 1712 Fg(-1) at a current density of 1 Ag-1 with excellent cyclic stability. The excellent supercapacitor performance of NCS nanosheets can be attributed to its rich redox reactions as well as high transport rate for both electrolyte ions and electrons. (C) 2016 Elsevier B.V. All rights reserved.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

Iron-carbon nanohybrid particles as environmentally benign electrode for supercapacitor - Ratha, Satyajit; Vernekar, Dnyanesh; Sivaneri, Kavin; Jagadeesan, Dinesh; Rout, Chandra Sekhar (Journal of Solid State Electrochemistry, 2017)
In this work, we report the synthesis and electrode applications of iron-carbon nanohybrid particles prepared by carbonization of a nanocomposite of FeOOH nanoneedles and melamine-formaldehyde resin. The chemical composition and microstructure of the material have been characterized using ICP-AES, FT-IR, XRD, FESEM, TEM and XPS. The supercapacitor properties of the MF-Fe-C are studied in detail. A thorough comparison of the supercapacitor performances of MF-Fe-C and bare MF-C has been carried out through detailed electrochemical characterisations employing both two and three-electrode techniques. The nanohybrid showed an enhanced energy density of 127.75 WhKg⁻¹, specific capacitance of ∼408 F g⁻¹ at 1 mVs⁻¹ scan rate, and excellent cyclic stability even after 1000 charge-discharge cycles, making it an intriguing material for high energy density supercapacitor devices.

Improved nonenzymatic glucose sensing properties of Pd/MnO2 nanosheets: synthesis by facile microwave-assisted route and theoretical insight from quantum simulations - Ponnusamy, Rajeswari; Gangan, Abhijeet; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Physical Chemistry B, 2018)
The electrocatalytic properties of manganese oxide (MnO2) can be improved significantly by making hybrids/composites with noble metals (Au, Pd). Here, efforts have been made to synthesize the MnO2/Au and MnO2/Pd nanocomposites by a facile, rapid microwave irradiation method. The products characterized by X-ray diffraction and transmission electron microscopy exhibited their tetragonal phase and nanosheet morphology. The efficiency of the prepared composite materials as glucose sensor was tested by cyclic voltammetry and chronoamperometry measurements, and the results are discussed. The study revealed that successful modification of MnO2 by Pd led to excellent sensing performance by the reduction of size and the synergistic effect between MnO2 and PdO, which expedites the electron transfer. Besides, the wide detection range, good selectivity, and stability demonstrate its robustness in the design of electrochemical sensor platform. To get theoretical insight into the excellent sensing performance of MnO2/Pd, we have performed detailed density functional theory simulations to explore the charge transfer and bonding mechanism of glucose on MnO2 and Pd/Au-doped MnO2 surface. Pd is bonded strongly on MnO2 and makes MnO2/Pd more conducting due to the enhancement of density of states near Fermi level. The higher binding energy of glucose and enhanced charge transfer from glucose to Pd-doped MnO2 compared to bare MnO2 infer that Pd-doped MnO2 possess superior charge-transfer kinetics, resulting in higher glucose sensing performance, which supports our experimental observations.

Temperature and pressure dependent Raman spectroscopy of plasma treated multilayer graphene nanosheets - Pawbake, Amit S.; Mishra, K. K.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Ravindranathan, T. R.; Rout, Chandra Sekhar; Late, Dattatray J. (Diamond and Related Materials, 2018)
Understanding of the fine structure at the atomic level and properties of graphene by creating defects is important from the point of view of thermal and stress management. Here we report Raman spectroscopic studies on pristine and plasma treated multilayer graphene to explore the remarkable structure and phonon properties with temperature and pressure. Temperature dependent studies illustrate monotonic softening of G and G′ bands in the temperature range 78 to 573 K. This process can be of fundamental importance in other promising and emerging nano and heterostructured materials. The pressure dependent Raman spectroscopic investigations on G-band of these samples were carried out up to 25 GPa using a diamond anvil cell. Comparatively weak and more compressible nature of the G band (E2g in-plane mode) as a function of applied pressure is found in plasma treated graphene. After pressure release, the samples recover to their original ordered structure. The present study is important for further understanding of the fine structure, properties and effect of defects in graphene, which can affect the atomic bonds, thermal expansion, specific heat, and thermal conductivity as well.
Keywords: graphene; high pressure; Phonon; Plasma treated graphene; Raman spectroscopy

Development of pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites for supercapacitor electrodes - Gote, Gorkshnath H.; Pathak, Mansi; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2019)
Pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites were synthesized via a facile hydrothermal method. Characterization techniques such as XRD, FESEM, HRTEM and XPS were used to explore the structural, morphological and electronic properties. Furthermore, electrochemical characterizations including cyclic voltammetry (CV), the galvanostatic charge-discharge (GCD) method, and electrochemical impedance spectroscopy (EIS) were performed to investigate the supercapacitance behaviour of the synthesized materials. Interestingly, the Au-decorated Bi2O3/Bi2WO6 nanocomposite showed a higher capacitance of 495.05 F g(-1) (1 M aqueous KOH electrolyte) with improved cycling stability (99.26%) over 2000 cycles, measured at a current density of 1 A g(-1), when compared to the pristine Bi2O3/Bi2WO6 composite (capacitance of 148.81 F g(-1) and good cycling stability (95.99%) over 2000 cycles at a current density of 1 A g(-1)). The results clearly reveal that the decoration of the Bi2O3/Bi2WO6 composite with Au nanoparticles enhances its supercapacitance behaviour, which can be attributed to an increase in electrical conductivity, good electrical contact between the electrode and electrolyte, and an increase in effective area. The Au-decorated Bi2O3/Bi2WO6 nanocomposite can be considered as an electrode material for supercapacitor application.

Experimental and density functional theory investigations of catechol sensing properties of ZnO/RGO nanocomposites - Ponnusamy, Rajeswari; Venkatesan, Rajiu; Gangan, Abhijeet; Samal, Rutuparna; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2019)
Catechol, an essential industrial feedstock is one of the major environmental pollutant which causes several health issues including skin irritation, eye damage and genetic defects. In this work, we have investigated the catechol sensing performance of ZnO/RGO composites for its quantitative detection. ZnO/RGO composite showed superior electron transfer kinetics, sensitivity (162.04 mu A mM cm(-2)) and lower detection limit (47 nM) than that of bare ZnO nanoparticles. Further, the change in the zeta potential towards the lower negative demonstrated the strong electrostatic interaction between ZnO-RGO and catechol where it is converted as 1, 2 Benzoquinone through redox reactions. By using state of the art of Density Functional Theory simulations, we have demonstrated the interaction of catechol molecule on various ZnO clusters and RGO supported ZnO clusters. The strong bonding between p orbital of O atom of catechol and d orbital of Zn atom and its charge transfer facilitate the oxidation of catechol molecule. In the presence of RGO, the binding energy of catechol and charge transfer increases which qualitatively infer that RGO/ZnO exhibits higher sensitivity compared to bare ZnO and in consistency with the experimental observations.

Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids

Fundamentals and sensing applications of 2D materials - Hywel, Morgan; Rout, Chandra Sekhar; Late, Dattatray J. (Elsevier, 2019)
Fundamentals and Sensing Applications of 2D Materials provides a comprehensive understanding of a wide range of 2D materials. Examples of fundamental topics include: defect and vacancy engineering, doping and advantages of 2D materials for sensing, 2D materials and composites for sensing, and 2D materials in biosystems. A wide range of applications are addressed, such as gas sensors based on 2D materials, electrochemical glucose sensors, biosensors (enzymatic and non-enzymatic), and printed, stretchable, wearable and flexible biosensors. Due to their sub-nanometer thickness, 2D materials have a high packing density, thus making them suitable for the fabrication of thin film based sensor devices.

Photo sensor based on 2D materials - Late, Dattatray J.; Bhat, Anha; Rout, Chandra Sekhar (Fundamentals and Sensing Applications of 2D Materials, 2019)
This chapter starts with a general introduction to the interaction of light with matter and use of this principle for sensing. Photo-sensing devices based on two-dimensional (2D) materials are compared to conventional designs and their respective differences discussed in detail. A range of 2D materials are introduced with a generic comparison based on their individual properties and importance to the generation of a photoresponse. Besides transition-metal dichalcogenides, the chapter also deals with black phosphorous photosensor devices. Different heterostructure architectures based on 2D layered structures are investigated and their role in next generation optoelectronics is discussed.

Synthesis of a 3D free standing crystalline NiSex matrix for electrochemical energy storage applications - Dinara, Syed Mukulika; Samantara, Aneeya K.; Das, Jiban K.; Behera, J. N.; Nayak, Saroj K.; Late, Dattatray J.; Rout, Chandra Sekhar (Dalton Transactions, 2019)
The electrochemical performance for energy storage of three-dimensional (3D) self-supported heterogeneous NiSex cubic-orthorhombic nanocrystals grown by a facile one-step chemical vapour deposition (CVD) approach on Ni foam substrates has been explored. NiSex shows a high specific capacitance of 1333 F g(-1) with ultra-high energy (105 W h kg(-1)) and power (54 kW kg(-1)) densities. Furthermore, by integrating the as-grown NiSex as the anode and reduced graphene oxide as the cathode, a hybrid super-capacitor (HSC) prototype with a coin cell configuration has been fabricated. The device shows better capacitance (40 F g(-1)) with high energy (22 W h kg(-1)) and power (5.8 kW kg(-1)) densities and robust cycling durability (similar to 88% capacitance retention after 10 000 repeated cycles). For practical reliability of the as-fabricated HSC, a red LED has been illuminated by connecting it with two charged coin cells. These outstanding performances of the HSC prove to be promising for applications in high energy storage systems.

Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template